1987
DOI: 10.1037/0022-006x.55.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Stress management in the health care setting: Matching interventions with patient coping styles.

Abstract: Forty-six patients about to undergo preprosthetic oral surgery were presented with either a problemfocused, emotion-focused, or mixed-focus stress management intervention. The mixed-focus intervention produced the best overall response to surgery; the emotion-focused intervention produced the lowest adjustment levels. The Krantz Health Opinion Survey Information scale was the best overall predictor of response to surgery in conjunction with treatments. Better adjustment and satisfaction and lower self-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 28 publications
(47 reference statements)
6
64
0
2
Order By: Relevance
“…It is notable that people differ in their desire for information about health-related issues and in the degree to which they want to be directly involved in their own health care (Krantz, Baum, & Wideman, 1980). These preferences can exert a substantial impact on individual distress prior to and during medical procedures, and interventions that are congruent with patient preferences for information and involvement are more effective than are strategies that are insensitive to these individual differences (Auerbach, Martelli, & Mercuri, 1983;Martelli, Auerbach, Alexander, & Mercuri, 1987).…”
mentioning
confidence: 96%
“…It is notable that people differ in their desire for information about health-related issues and in the degree to which they want to be directly involved in their own health care (Krantz, Baum, & Wideman, 1980). These preferences can exert a substantial impact on individual distress prior to and during medical procedures, and interventions that are congruent with patient preferences for information and involvement are more effective than are strategies that are insensitive to these individual differences (Auerbach, Martelli, & Mercuri, 1983;Martelli, Auerbach, Alexander, & Mercuri, 1987).…”
mentioning
confidence: 96%
“…Moreover, detailed medical information provided by the anaesthetist only served to increase anxiety for some patients. Martelli et al (1987) studied 46 patients undergoing oral surgery and local anaesthesia and concluded emotional focused coping strategies was the most effective method for patients who were very anxious and in a situation where there was little possibility for personal choice. Anderson (1987), utilising emotional and behavioural measures when surveying patients prior to cardiac surgery concluded information alone did not reduce anxiety although it did help to increase feelings of control.…”
Section: Indicators Against Information Provisionmentioning
confidence: 99%
“…stress results from the physical trauma of surgery (Wolfer and Davies 1970, Ramsay 1972, Wallace 1984, Martelli et al 1987, O`Hara et al 1989. Wallace (1984) discovered even minor surgery to be stressful.…”
Section: Anxiety Managementmentioning
confidence: 99%
“…It seems that such interventions would be more effective if they are designed based on coping style of each patient (10). Nurses need to personally assess their patients and establish an open relation with them (11).…”
Section: Introductionmentioning
confidence: 99%